1995
DOI: 10.1002/jez.1402720203
|View full text |Cite
|
Sign up to set email alerts
|

CO2 transport in catheterized hydrothermal vent tubeworms, Riftia pachyptila (vestimentifera)

Abstract: Isolated plumes and vestimenta of the tubeworm Riftia pachyptila were perfused to determine the form in which carbon is transported to the animal's symbionts via the circulatory system. Catheters supplying colored saline were inserted into an afferent blood vessel while samples were collected from the efferent vessel. During perfusion, the plumes were immersed in sea water containing radiolabeled C02. The effluent showed radioactivity in inorganic carbonate (X C02, sum of all forms), malate, and succinate. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Organic carbon can be passed from symbiont to host either by the active or passive transfer of small organic molecules from the symbiont cells, by host digestion of the symbionts, or a combination of both . In Bathymodiolus mussels incubated with 14 CH4, labelled organic carbon only appeared in the host after 1-5 days, indicating that the transfer of organic carbon from the symbiotic methanotrophs to the host occurs by the digestion of the symbionts , rather than the translocation of small organic compounds, which is rapid and occurs within seconds in the hydrothermal vent tubeworm Riftia pachyptila (Felbeck and Turner, 1995). The occurrence of degenerate stages of the methanotrophic symbionts in transmission electron micrographs of Bathymodiolus mussels is also consistent with digestion as a means of carbon transfer from symbiotic methane oxidizers to their hosts (Barry et al, 2002).…”
Section: Transfer Of Carbon From Symbiont To Hostmentioning
confidence: 99%
“…Organic carbon can be passed from symbiont to host either by the active or passive transfer of small organic molecules from the symbiont cells, by host digestion of the symbionts, or a combination of both . In Bathymodiolus mussels incubated with 14 CH4, labelled organic carbon only appeared in the host after 1-5 days, indicating that the transfer of organic carbon from the symbiotic methanotrophs to the host occurs by the digestion of the symbionts , rather than the translocation of small organic compounds, which is rapid and occurs within seconds in the hydrothermal vent tubeworm Riftia pachyptila (Felbeck and Turner, 1995). The occurrence of degenerate stages of the methanotrophic symbionts in transmission electron micrographs of Bathymodiolus mussels is also consistent with digestion as a means of carbon transfer from symbiotic methane oxidizers to their hosts (Barry et al, 2002).…”
Section: Transfer Of Carbon From Symbiont To Hostmentioning
confidence: 99%
“…The specific cell size and macromolecular composition is also correlated with growth rate, but cell-form modulations are related to nutrition only. Symbiont nutrition, which in this case means supply of chemicals for chemoautotrophy, is provided by the blood flow from the periphery towards the center (van der Land & Narrevang 1975, 1977Jones 1988;Felbeck & Turner 1995). Bright et al (2000) argued that a gradient in chemicals for chemoautotrophy is not present because carbon incorporation rates are high in the center and in the periphery.…”
Section: Growth Rate and Physiological State Of The Symbiont Morphotypesmentioning
confidence: 99%
“…Biochemical gradients would result from the fact that the animal's circulatory system supplies the symbiotic bacteria with their chemoautotrophic substrates. Morphological investigations first suggested that the direction of blood flow in vestimentiferans is from the periphery to the center of each lobule (van der Land & Norrevang 1975, 1977Jones 1988), which was later confirmed with live animals (Felbeck & Turner 1995). A 14C bicarbonate autoradiographic study showed that after 1-3 h of pulse incubations, the carbon incorporation rate of the central zone was almost as high as in the peripheral zone, but was lower in the median zone (Bright et al 2000).…”
mentioning
confidence: 98%
“…The plumes in tube worms have been reported so far to function as gills and to be the site of gas exchange, including hydrogen sulfide (Childress et al, 1984;Felbeck and Turner, 1995;Goffredi et al, 1997a, b andAndersen et al, 2002). On the other hand, the functions of the tentacles (beard) in beard worms have not been examined, although the plume in tube worms and the tentacles in beard worms are embryologically homologous (Southward, 1988).…”
Section: Introductionmentioning
confidence: 99%